Perspektif Manajemen Keuangan Syariah: Peran Gender dalam Pengelolaan Keuangan Rumah Tangga di Maluku - Amina Saramoko; Arizal Hamizar; Hanifah (Univiversitas Dr. Djar Wattiheluw, 2025)
This study examines the role of women in household financial management in the Maluku community, focusing on women's dominance in managing daily finances despite Islamic teachings assigning men as the heads of the household. A qualitative approach was used with in-depth interviews as the data collection technique, highlighting household financial management, the roles of family members in decision-making, and the social and cultural factors influencing role distribution. The findings show that women play a more dominant role in managing budgets, savings, and debts, influenced by the social and cultural factors in Maluku and women's involvement in the workforce. Nevertheless, men still play a role in major financial decisions such as property purchases and investments. This phenomenon reflects an adaptive and collaborative division of roles within the family, while still respecting Islamic principles related to male leadership in the household.